2003
DOI: 10.1177/153537020322800912
|View full text |Cite
|
Sign up to set email alerts
|

Soy Protein with or Without Isoflavones, Soy Germ and Soy Germ Extract, and Daidzein Lessen Plasma Cholesterol Levels in Golden Syrian Hamsters

Abstract: Dietary isolated soy protein (ISP, containing approximately equal amounts of daidzein and genistein), ethanol-extracted ISP (ISP (-)), soygerm or soygerm extract (containing large amounts of daidzein and glycitein and little genistein) and the isoflavone, daidzein, were hypothesized to lessen plasma cholesterol in comparison with casein. Sixty male and 60 female golden Syrian hamsters (6-8 weeks of age) were randomly assigned to six treatments fed for 10 weeks. Four of the experimental diets (ISP, daidzein, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
2
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 33 publications
7
48
2
4
Order By: Relevance
“…The results of this work are related to other studies that use vegetable foods for glycemic and lipid control, aiming at the prevention and treatment of chronic degenerative diseases (CAMACHO, 1996;JORGE et al, 1998;SONG;LEE, 2003;FIGUEIREDO;MODESTO-FILHO, 2008). These diseases are on the rise, for the globalized economy has led to new worldwide trends in the nutritional sector, contributing toward rapid changes in dietary patterns, with increasing consumption of foods rich in fats and sugars and a decline in the consumption of foods essential to health and in the practice of physical activities.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The results of this work are related to other studies that use vegetable foods for glycemic and lipid control, aiming at the prevention and treatment of chronic degenerative diseases (CAMACHO, 1996;JORGE et al, 1998;SONG;LEE, 2003;FIGUEIREDO;MODESTO-FILHO, 2008). These diseases are on the rise, for the globalized economy has led to new worldwide trends in the nutritional sector, contributing toward rapid changes in dietary patterns, with increasing consumption of foods rich in fats and sugars and a decline in the consumption of foods essential to health and in the practice of physical activities.…”
Section: Resultsmentioning
confidence: 96%
“…Figueiredo and Modesto-Filho (2008) determined the effects of defatted sesame (Sesamum indicum L.) flour on the glycemic levels and weight control of diabetes type 2 patients. Soy (SONG;LEE, 2003) and eggplant (CAMACHO, 1996;JORGE et al, 1998) have been widely studied and their consumption has been associated with beneficial effects on dyslipidemias.…”
Section: Biochemical Measurementsmentioning
confidence: 99%
“…Type 2 diabetes mellitus, atherosclerosis, heart disease and cerebral vascular accidents, and also constitute an independent risk of coronary artery disease (Manco et al, 2004). Plants such as soybean (Song and Lee, 2003), eggplant (Camacho et al, 1996), green tea (Kuo et al, 2005) and others are widely cited in the literature as the targets of studies relating to hypocholesterolemic effects. M. piperita is considered one of the ten plants most commonly used by the Brazilian population for therapeutic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The use of these plants to control blood sugar and lipid levels in plasma is widespread and many studies have shown that some plants do have beneficial effects (Song and Lee, 2003;Zou et al, 2005). Hypercholesterolemia and low HDL-c (high density lipoprotein-cholesterol) levels are very common today and are often associated with endothelium dysfunction and inflammation, which are often followed by atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies investigated the cholesterol-lowering effects of pure synthetic isoflavones or isoflavones isolated from soybean fractions (8,(17)(18)(19). Ovariectomized rats gavaged with the isolated pure isoflavone glucosides daidzin (25 or 50 mg/ (kg body weight/day)) or glycitin (50 mg/(kg body weight/day)) showed significantly lesser plasma total cholesterol and triglyceride concentrations compared with casein-fed rats (17).…”
Section: Introductionmentioning
confidence: 99%